Hematobin is a novel immunomodulatory protein from the saliva of the horn fly Haematobia irritans that inhibits the inflammatory response in murine macrophages - Martin Breijo (Parasites & Vectors, 2018)
Abstract Background The horn fly Haematobia irritans is a blood-sucking ectoparasite responsible for substantial economic loss of livestock. Like other hematophagous arthropods species, the successful blood-feeding of H. irritans is highly dependent on the modulation of the host’s hemostasis and immune system. Here, we evaluated the biological activity of hematobin (HTB), a protein recently identified in the H. irritans saliva, on macrophage biology. The goal was to understand the putative interactions between the components of H. irritans saliva and the early host immune responses. Results Thioglycolate-elicited peritoneal macrophages from BALB/c mice were stimulated by lipopolysaccharide (LPS) plus interferon-γ (IFN-γ) in the presence or absence of recombinant HTB. The presence of the salivary protein in the cultures inhibited nitric oxide production and decreased the inducible nitric oxide synthase (iNOS) expression induced by LPS plus IFN-γ. The tumor necrosis factor-α (TNF-α) and interleukin-12p40 (IL-12p40) levels were also reduced in the macrophages pre-incubated with HTB; these findings correlated to the decreased NF-κB expression. The biological activities described here were not associated with changes in annexin V binding to macrophages suggesting that HTB does not induce cell death. In addition, the activity of HTB seems to be specific to macrophages because no changes were observed in lymphocyte proliferation or cytokine production. Conclusions We describe here the first bioactive salivary protein of H. irritans. We characterized its ability to modulate macrophage inflammatory response, and the results can help explain how horn flies modulate the host immune system to feed on blood.